The effect of leaves extract Sambung Nyawa leaves (G. procumbens L.) against Crop Cabbage Caterpillar mortality (C. binotalis Zell.) - Wirda Yuliani; Safrida safrida; Mimie Saputri; Supriatno Supriatno; Abdullah Abdullah (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
Crop Cabbage Caterpillars (Crocidolomia binotalis Zell.) are included in the orderLepidoptera. C. binotalis pest is a pest that attacks mustard plants. Pest controlefforts carried out by farmers in Indonesia still using syntetic insecticides thatcausing negatif effects on the environment, human health and increasing pestpopulations. Therefore, controlling which has been developed is using bioinsecticides namely natural bioactive compounds derived from plants one of which isa plant are plants Sambung Nyawa leaves (Gynura procumbens L.). The purpose ofthis study was to determine the effect of leaves extract Sambung Nyawa leaves (G.procumbens L.) against Crop Cabbage Caterpillar mortality (C. binotalis Zell.) anddetermine the concentration (LC 50) Sambung Nyawa leaves extract (G. procumbensL.) effective on mortality Crop Cabbage Caterpillar (C. binotalis Zell.). The methodused is an experimental method through a quantitative approach with a completelyrandomized design pattern (CRD) consisting of 6 treatments and 4 repetitions.Toxicity tests for Crop Cabbage Caterpillars (C. binotalis Zell.) was carried out on afield scale. Data were analyzed using Variant Analysis (ANAVA) and carried outfurther tests in the form of real difference test (LSD) and probit regression analysis.Research results F arithmetic gt; F table = 537.87 gt; 2.77 using α = 0.05. Theadministration of the Sambung Nyawa leaves (G. procumbens L.) extractsignificantly affected the mortality of Crop Cabbage Caterpillars (C. binotalis Zell.).The best concentration extract which caused 50% (LC 50) death of Crop CabbageCaterpillars (C. binotalis Zell.) is 3,000 ppm. Keywords: Sambung Nyawa leaves, Bioinsecticide, Crop Cabbage Caterpillars. Ulat Crop Kubis (Crocidolomia binotalis Zell.) termasuk dalam ordo Lepidoptera. Hama C. binotalis merupakan hama yang menyerang tanaman sawi. Usaha pengendalian hama yang dilakukan oleh petani di Indonesia masih sering menggunakan insektisida sintetis sehingga menyebabkan efek negatif bagi lingkungan, kesehatan manusia, dan meningkatnya populasi hama. Saat ini pengendalian Ulat Crop Kubis (C. binotalis Zell.) dengan penggunaan Bioinsektisida yaitu senyawa bioaktif alamiah dari tumbuhan, salah satu tumbuhan itu adalah tumbuhan Sambung Nyawa (Gynura procumbens L.). Tujuan dari penelitian ini adalah mengetahui pengaruh ekstrak daun Sambung Nyawa (G. procumbens L.) terhadap mortalitas hama Ulat Crop Kubis (C. binotalis Zell.) serta mengetahui Lethal Consentrastion (LC50) pemberian ekstrak daun Sambung Nyawa (G. procumbens L.) terhadap mortalitas Ulat Crop Kubis (C. binotalis Zell.). Metode yang digunakan  adalah metode Eksperimental melalui pendekatan kuantitatif dengan pola Rancangan Acak Lengkap (RAL) yang terdiri dari 6 perlakuan dan 4 kali pengulangan. Uji toksisitas terhadap Ulat Crop Kubis (C. binotalis Zell.) dilakukan pada skala lapangan. Data akan dianalisis menggunakan Analisis of Varian (ANOVA) kemudian dilakukan uji lanjutan yaitu uji beda nyata terkecil (BNT) dan dilakukan analisis regresi probit. Pemberian ekstrak daun Sambung Nyawa (G. procumbens L.)  berpengaruh nyata terhadap mortalitas ulat Crop Kubis (C. binotalis Zell.) konsentrasi yang paling efektif ialah konsentrasi 5.000 ppm yang menyebabkan kematian hingga 100%. Konsentrasi ekstrak yang menyebabkan 50% (LC50) kematian Ulat Crop Kubis (C. binotalis Zell.) adalah 3.000 ppm. Kata kunci: Daun Sambung Nyawa, Bioinsektisida, Ulat Crop Kubis.